Analysis of Hospital Reporting Compliance with National Quality Indicators (NQI) on the Ministry of Health's SIRS Online Platform: Determinants and Implications for Service Transparency - Rahayu Tri Nuritasari; Arlia; Miftahul Jannah; Rafika Aini; Mirza Aulia (CV. Get Press Indonesia, 2025)
Hospital reporting compliance with the National Quality Indicators (NQI) on the Ministry of Health’s SIRS Online platform plays a key role in evaluating and managing Indonesia’s healthcare quality. This study assesses the level of hospital reporting adherence, identifies significant influencing factors, and explores implications for service transparency. Using cross-sectional quantitative analysis of national secondary data from 2019 to 2024, the research analyzed data from all active hospitals reporting on SIRS. Descriptive and regression analyses revealed a compliance increase from 58% to 72%, with significant variation across provinces and hospital classes. Key determinants positively impacting compliance were human resource capacity, digital information technology support, and leadership commitment. Persistent challenges include infrastructural limitations, cultural resistance, and inconsistent data quality. Strengthening workforce skills, advancing interoperable digital systems, and fostering a transparent reporting culture are essential to improve accountability and public trust. The study underscores the critical need for collaboration between the government and hospital institutions to optimize reporting systems, thereby enhancing healthcare service quality across Indonesia.